Serviços logísticos em canais de distribuição: um estudo de caso no setor de alimentos - Frederico Luiz Vieira (2009)
The aim of this work is to investigate and to describe the relationships between the quality of logistic services, performance and satisfaction of customers in the relationship structures enters a national company with performance in the nourishing sector and its base of customerslocated in the city of Belo Horizonte. 146 valid cases in the sample had been gotten, being that the data had been collected from one survey carried through in the period of August to October of 2008. The segmentation of customers considered the sales volume between thesupplier and its customers, drawing up of the Pareto rule (20/80). The model of Mentzer et al. (1999) it served of base for the evaluation of the perception of the customers in relation to the logistic services offered by the supplier. The treatment of the data involved the application ofdifferent techniques of descriptive and multivariate statistics. Between the multivariate techniques, they had been developed, beyond the confirmatory factorial and of the tests of adjustment of the scales of the research instrument, the modeling of structural equations, inthis last case from the same logic of reflective constructs that was used originally in the work of Mentzer et. al. (1999). The data and information gotten by means of one search of the type survey, in the region where if it found the population-target of the research, they had allowedto compare the performance and gaps of performance following itself it strategy of segmentation of customers of the supplying company, as well as the analysis of the associations between the quality of the logistic services and the satisfaction of the customers with such logistic services. It enters the results of the research, the studied case demonstratedin such a way not to exist differences statistical significant of the performance how much of gaps of performance following itself it strategy segmentation of customers. The results had also indicated the existence of statistical significant associations between the quality of thelogistic services offered and the satisfaction of the customers, considering themselves each grouping of segmentation of customers. The results gotten in this research for the esteem of the structural model of the constructs had presented bigger loads of what gotten in the studyof Mentzer et al. (1999). The results demonstrate that the latent variable logistic services quality possess the capacity to explain significant part of its factors, being able to vary of 36% 84%.